Analysis of the impact of managers' psychological deviation on information disclosure and irrational overseas investment after IFRS convergence - Zhong, Bin; Soh, Wei Ni; Ong, Tze San; Muhamad, Haslinah; He, ChunXi (Elsevier, 2024)
Based on a sample of 6485 firms listed on the Chinese Shanghai and Shenzhen A-shares between 2017 and 2021, the effect of managers' psychological deviation on irrational investment is empirically tested. The higher the managers’ confidence, the lower the investment efficiency. The level of irrational investment in listed companies increases with the degree of managers’ risk appetite. The improvement of disclosure quality of enterprises after IFRS convergence in China can weaken irrational investment triggered by managers' overconfidence. The information disclosure quality by companies can manage the irrational investment behavior that is exacerbated by the high degree of managers’ risk appetite.